Hubungan Antara Pengetahuan Tentang Penyakit Infeksi Dengan Status Imunitas Mahasiswa - Susmitha, Eva; Dorta Simamora (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2024)
Background: Infectious disease is one of the problems in the health sector which from time to time continues to grow. One of the efforts to increase immunity by increasing knowledge and behaviour so as to avoid infectious diseases. This study aims to determine the relationship between knowledge about infectious diseases and immunity status in FH UWKS students class of 2022. Methods: This research is included in observational research which is cross-sectional in nature. The population of this research was the students of Faculty of Law UWKS class of 2022 (120 students). The determination of the number of samples in this research used the gSlovin's formula, which was a total of 93 students, with a simple grandom sampling technique. The independent variable in this study was knowledge about infectious diseases and the dependent variable in the following study was community status. Data analysis technique using chi square. Result: The results concluded that FH UWKS Batch 2022 students had a level of knowledge about infectious diseases in the high category, namely 58,1% or 54 respondents, their immunity status was also mostly in the very good category, namely 84,9% or 79 respondents. Conclusion: This study also shows that there is a strong relationship between knowledge about infectious diseases and immunity status in FH UWKS Batch 2022 students, both variables are in the strong category with a value of 0.611